1999
DOI: 10.1042/bj3370305
|View full text |Cite
|
Sign up to set email alerts
|

Expression and subcellular localization of the ryanodine receptor in rat pancreatic acinar cells

Abstract: The ryanodine receptor (RyR) is the principal Ca2+-release channel in excitable cells, whereas the inositol 1,4,5-trisphosphate (InsP3) receptor (InsP3R) is primarily responsible for Ca2+ release in non-excitable cells, including epithelia. RyR also is expressed in a number of non-excitable cell types, but is thought to serve as an auxiliary or alternative Ca2+-release pathway in those cells. Here we use reverse transcription PCR to show that a polarized epithelium, the pancreatic acinar cell, expresses the ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
35
0
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(41 citation statements)
references
References 47 publications
5
35
0
1
Order By: Relevance
“…Ashby et al [21] showed that both IP 3 and ryanodine-sensitive channels are present in the apical pole of the acinar cell. This finding is in agreement both with other functional studies that place these receptors in the apical pole [7,8] and with the results of immunostaining of the acinar cells [9,10,26]. Uncaging of Ca 2+ in the apical pole triggered an increase in cytosolic Ca 2+ that originates in the apical pole, and spreads to the basal pole.…”
Section: Caged Compounds In the Study Of Cell Signallingsupporting
confidence: 93%
“…Ashby et al [21] showed that both IP 3 and ryanodine-sensitive channels are present in the apical pole of the acinar cell. This finding is in agreement both with other functional studies that place these receptors in the apical pole [7,8] and with the results of immunostaining of the acinar cells [9,10,26]. Uncaging of Ca 2+ in the apical pole triggered an increase in cytosolic Ca 2+ that originates in the apical pole, and spreads to the basal pole.…”
Section: Caged Compounds In the Study Of Cell Signallingsupporting
confidence: 93%
“…Following more intense stimulation, the Ca 2ϩ signals can propagate in a manner typical of a true "wave" toward the basal aspects of the cell; i.e., constant wave speed typical of an "all or nothing" phenomenon dependent on Ca 2ϩ -induced Ca 2ϩ release (CICR) (17,24,25,27,35,45). CICR can occur through either InsP 3 R or through the classical CICR channel, the ryanodine receptor (RyR), which is also expressed in exocrine cells (14,26,39,53). In pancreatic acinar cells, two general models have been proposed to account for the propagation of the Ca 2ϩ wave.…”
mentioning
confidence: 99%
“…The rat pancreatic acinar cells express multiple isoforms of RyR Ashby and Tepikin 2002;Ashby et al 2003) but predominance with type II RyR (Leite et al 1999). The dynamic model of RyR has not been yet developed for pancreatic acinar cell.…”
Section: Discussionmentioning
confidence: 98%
“…In the pancreatic acinar cell the RyR receptors are distributed throughout the cell (Leite et al 1999;Ashby and Tepikin 2002;Ashby et al 2003). Thus it is important to incorporate RyR receptors in our model.…”
Section: The Ryr Modelmentioning
confidence: 99%